The relation between ankle-brachial index (ABI) and coronary artery disease severity and risk factors: an angiographic study - Masoumeh Sadeghi; Ramin Heidari; Baharak Mostanfar; Aliakbar Tavassoli; Farshad Roghani; Safoura Yazdekhasti (ARYA Atherosclerosis, 2011)
BACKGROUND: The current study aims to determine the relation between ankle–brachial index (ABI) and angiographic findings and major cardiovascular risk factors in patients with suspected coronary artery diseases (CAD) in Isfahan. METHODS: In this cross-sectional descriptive-analytic research, patients with suspected CAD were studied. Characteristics of studied subjects including demographics, familial history, past medical history and atherosclerotic risk factors such as diabetes mellitus, hypertension, hyperlipidemia and smoking were obtained using a standard questionnaire. ABI was measured in all studied patients. ABI ≤ 0.9 (ABI+) was considered as peripheral vessel disease and ABI > 0.9 (ABI-) was considered as normal. Then, all studied patients underwent coronary artery angiography. The results of the questionnaire and angiographic findings were compared in ABI+ and ABI- groups. Data were analyzed by SPSS 15 using ANOVA, t-test, Spearman's rank correlation coefficient, and discriminant analysis. RESULTS: In this study, 125 patients were investigated. ABI ≤ 0.9 was seen in 25 patients (20%). The prevalence of ABI+ among men and women was 25.9% and 7.5%, respectively (P = 0.01). The prevalence of atherosclerotic risk factors was significantly higher in ABI+ patients than in ABIones (P < 0.05). ABI+ patients had more significant stenosis than ABI- ones. The mean of occlusion was significantly higher in ABI+ patients with left main artery (LMA), right coronary artery (RCA), left anterior descending artery (LAD), diagonal artery 1 (D1) and left circumflex artery (LCX) involvements (P < 0.05). CONCLUSION: The findings of this research indicated that ABI could be a useful method in assessing both the atherosclerotic risk factors and the degree of coronary involvements in suspected patients. However, in order to make more accurate decisions for using this method in diagnosing and preventing CAD, we should plan further studies in large sample sizes of general population. Keywords: Ankle–Brachial Index, Angiography, Atherosclerotic Risk Factors.